One leg at a time - Vivier, Lincky Elmé (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
This collection of poems explores the boundaries between certainty and uncertainty, between the desire for meaning and the destabilisation of meaning. The content encompasses everyday life, love and loss, and the ambiguities are reflected in the forms used, so that, for instance, the linear continuity of narrative and the musicality of the lyric may be juxtaposed with the fragmented and imagistic leaps of the associative poem.
Keywords: Creative writing (Higher education) -- Research -- South Africa; Creative writing -- Poetry; South African poetry (English) -- Study and teaching (Higher); South African poetry (English) -- 21st century; English language -- Writing